Application Development of Building Maintenance Periodization on Surabaya City Government Property - Putra, I Nyoman Dita Pahang; Suryani, Erma; Mudjahidin; Trigunarsyah, Bambang; Diyasa, I Gede Susrama Mas (Future Science, 2023)
Building maintenance is a very important activity and requires regular or scheduled implementation so that financial budgeting can be prepared and scheduled better. The building maintenance application is managed at the Regional Apparatus Work Unit through the Building Maintenance Section which inputs coding, building name, Final Hand Over (FHO) time, maintenance period, components and types of work, amount, unit cost, and construction cost. Observation data was collected on one hundred schools and government buildings for 5 years. Identify the components and types of work that require maintenance through interviews with the infrastructure division of each building that is surveyed. Observations and interviews are needed as a basis for determining the components and types of work that often occur in damage to each building after FHO. After the data is inputted, to prove the actual damage conditions to the buildings being reviewed, verification is required by the infrastructure division in each building. Verification consists of: building name, FHO time, maintenance period, components and types of work, quantity. The infrastructure division cannot see and change unit costs and development costs. Decision making on the implementation of building maintenance from the existing output is carried out by the Head of the Regional Apparatus Work Unit. Decisions taken by the Head of the Regional Apparatus Work Unit are expected to represent the priority scale of building maintenance that must be carried out by the Regional Apparatus Work Unit. In this building maintenance application, the total maintenance costs for each building and each month can be generated every year, and the total maintenance costs for the entire building and every month for each year, and the level of damage can be generated for each maintenance carried out on each building, and can the components and types of work to be carried out each month are known.